Counterpublics in the age of mediatisation: Local responses to Femen in the Arab world - Darmoni, Kaouthar; Witschge, Tamara (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
In this paper we analyse the impact of the mediatised strategy of the global protest group Femen. In addition to the concept of mediatisation, we employ the concept of counterpublics and find that Femen have limited impact in the Arab world due to a lack of embedment in local communities. We show how mediatisation of protest can hamper the dual function of counterpublic discourse and action. By focusing primarily outwardly and adopting dominant media logics (outwardly focused, interpublic discourse), Femen’s protest strategies result in a sensational and top-down message. This is not embedded in a conversation with local communities (the inwardly focused intrapublic function of counterpublic discourse) and as such results in much resistance in the Arab world. Moving beyond an analysis of Femen’s message to include local Arab responses, our analysis allows us insight into the lived experiences of mediatised protest, which suggest that Femen’s antagonistic actions foster alienation rather than empowerment.